1994
DOI: 10.1093/oxfordjournals.aje.a117194
|View full text |Cite
|
Sign up to set email alerts
|

Intraclass Correlation among Common Measures of Adolescent Smoking: Estimates, Correlates, and Applications in Smoking Prevention Studies

Abstract: Most adolescent smoking prevention studies employ designs in which classrooms, schools, school districts, or sometimes whole communities are assigned to treatment conditions while observations are made on individual students. The critical design feature in such community trials is the nesting of intact social groups within treatment conditions. This combination requires that the treatment effect be assessed against the between-group variance; unfortunately, that variance is usually larger than for randomly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 0 publications
5
65
0
Order By: Relevance
“…However, a few studies showed that schoollevel intraclass correlations for smoking and other health behaviors ranged from 0 to 0.075. [48][49][50] Intraclass correlation coefficients in relevant schoolbased studies often are small, 51 which enhances our confidence in our treatment effects.…”
Section: Discussionmentioning
confidence: 94%
“…However, a few studies showed that schoollevel intraclass correlations for smoking and other health behaviors ranged from 0 to 0.075. [48][49][50] Intraclass correlation coefficients in relevant schoolbased studies often are small, 51 which enhances our confidence in our treatment effects.…”
Section: Discussionmentioning
confidence: 94%
“…Less has been written, however, about the intraclass correlation as a parameter of interest with utility for investigators. Murray et al surveyed community-based studies of smoking interventions in classrooms of students and described variations in intraclass correlation within classrooms across the studies (22). Using data from the Health Survey for England, Guillford et al reported several levels of intraclass correlation from the district health authority to the household (23).…”
Section: Discussionmentioning
confidence: 99%
“…24 We assumed an intracluster correlation of Ļ = 0.01 based on a comparison with the mean Ļ found by Murray and associates 27 of Ļ = 0.006 in examining adolescent smoking behaviour. We also adjusted for a potential drop-out and noncompliance rate in the intervention group and a contamination rate in the control group (R o = 0.10).…”
Section: Methodsmentioning
confidence: 99%